Killing of Mycobacterium avium subspecies paratuberculosis within macrophages - Stabel Judith R; Bannantine John P (BMC Microbiology, 2002)
Abstract Background Mycobacterium avium subspecies paratuberculosis (M. paratuberculosis) is a facultative intracellular pathogen that resides within host macrophages during infection of ruminant animals. We examined survival of M. paratuberculosis infections within cultured macrophages to better understand the interplay between bacterium and host. Results Serial plating of M. paratuberculosis infected macrophage lysates on Herold's egg yolk medium showed that mycobacterial replication takes place between 0 and 24 hours post-infection. This initial growth phase was followed by a steady decline in viability over the next six days. Antibodies against M. paratuberculosis were affinity purified and used in conjunction with transmission electron microscopy to track the development of intracellular bacilli. Immunogold labeling of infected macrophages with antibody against M. paratuberculosis showed degraded intracellular mycobacteria that were unrecognizable by morphology alone. Conversely, when macrophages were heavily infected with M. paratuberculosis, no degraded forms were observed and macrophages were killed. Conclusions We present a general description of M. paratuberculosis survival within cultured macrophages using transmission electron microscopy and viability counts. The results of this study provides further insight surrounding M. paratuberculosis-macrophage infections and have implications in the pathogenesis of M. paratuberculosis, a pathogen known to persist inside cattle for many years.